Evaluasi Usability Dan Perbaikan User Interface Pada Aplikasi KRL Access Menggunakan Metode Human Centered Design (HCD) dan Post-Study System Usability Questionnaire (PSSUQ) - Ady Ramadhan Putra; Satrio Hadi Wijoyo; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Electric Train (KRL) as a mode of public transportation is still Jabodetabek people choice's. PT KCI (Kereta Commuter Indonesia) created the KRL Access application in 2015 with purpose to making it easier get information related to KRL schedules, route, and KRL positions. The researcher found several problems based on interviews and observations, including the inconsistent use of language, differences in application schedules with real-time conditions, and back buttons that did not function properly. From the problems found, the researchers evaluated the usability and improvement of the user interface using the HCD approach and the PSSUQ as questionnaire. After researcher get the evaluation results, the next step is to make a design improvement as a solution to the problem created based on several guidelines. The results of the comparison show a significant increase, where there was an increase in the aspect of effectiveness from 48% to 100%, then efficiency aspect from 11.85% increase to the 100%, and then user satisfaction aspect from 56.25% increase to 98.75%. The researcher concludes that the increase in value because the design improvement made by the researcher gives a higher user experience value than the initial design of the application.